Science and technology for the community of traditional beef cattle farmers who face animal feed problem - Budiyanto, Moch. Agus Krisno; Hadi, Samsun (Journal of Community Service and Empowerment, 2020)
The problem faced by IbM partner, Traditional Farmers Group located in the Village Sumbersari Poncokusumo Malang, is the the slow increase in weight gain per unit time of Brahman Cattle. To get ready to sell a decent weight of at least 500 kg, according to the Department of Agriculture, requires a maximum period of 6 months; however, the reality of Traditional Farmers Group located in the Village Sumbersari takes more than 12 months and some even 24 months. This is because the feed given to the Brahman cattle do not have good quality because it uses fresh straw. This IbM's goal is to provide a solution for farmers who face the problem of animal feed. The program was conducted in the Village Sumbersari Poncokusumo Malang East Java Province during May to October 2010 (6 months) involving 2 groups of partners and 20 traditional Brahman cattle breeders. The activities carried out consist of production training, animal feed production, and review of production results. The IbM activities that have been achieved are training, production practices, and action studies on 7 types of making preserved cattle feed from straw. Based on the results of the activity, it can be concluded that IbM partner breeders have improved knowledge, production skills, and action reviews in utilizing straw products as cattle feed.